IMPROVING STUDENT LEARNING OUTCOMES THROUGH ORIGAMI PAPER MEDIA FLAT BUILDING MATERIAL CLASS 2 PRIMARY SCHOOL - Nur Apida; Muhammad Faisal; Atika Sahriyanti (Global Journal Basic Education, 2026)
This study aims to improve student learning outcomes through the use of origami paper media on the material of flat shapes for grade 2 at UPT SPF SDI Pabaeng-Baeng 1. The type of research used in this study is Classroom Action Research (CAR). The sample of this study was 28 students. The data collection techniques used were tests and non-tests. This study was conducted in two cycles, each cycle consisting of two meetings. One research cycle includes planning, action, observation, and reflection activities. The results of this study indicate an increase in student learning outcomes through the use of origami paper media on the material of flat shapes for grade 2. In cycle I, there was an increase in the number of students who obtained complete learning outcomes, namely 64.3%. In cycle II, the number of students who obtained complete learning outcomes reached 82.1%. So it can be concluded that student learning outcomes can be improved through the use of origami paper media on the material of flat shapes for grade 2 at UPT SPF SDI Pabaeng-Baeng 1.